Caribbean Report 05-07-1990 - Crosskill, Hugh (anchor); Thompson, Pat (interviewee); Jessop, David (interviewee) (The British Broadcasting Corporation, 1990)
In a special edition of the Caribbean Report, David Jessop, Executive Director of the West India Committee and Pat Thompson, Executive Director of the Caribbean Association of Industry and Commerce express fears that the Caribbean region is unprepared for the challenges ahead. According to Jessop and Thompson, unless the Caribbean leaders and public and private sectors officials address the growing challenges of the region with a greater sense of urgency, the Caribbean will be left behind in the international arena. Developments that impact the sustainability of the Caribbean economies include the approach of 1992, the European Single Market, the events in Eastern Europe and the US free trade initiatives.
1. Headlines (00:00-00:43)
2. Is the Caribbean prepared for the economic challenges of the future? Hugh Crosskill interviews David Jessop, Executive Director of the London based West India Committee and Pat Thompson, Executive Director of the Caribbean Association of Industry and Commerce (00:44-15:00)
Special edition.
Keywords: Caribbean Area -- Economic aspects.; European Economic Community.; Free trade -- Caribbean Area.; European Union -- Caribbean Area.